Surface state of the dopamine RNA aptamer affects specific recognition and binding of dopamine by the aptamer-modified electrodes. Issue 12 (21st June 2015) - Álvarez-Martos, Isabel; Campos, Rui; Ferapontova, Elena E.
<x xml:space="preserve">Abstract</x> An electrochemical label-free aptasensor monitors physiological levels of dopamine with improved sensitivity when the aptamer surface coverage is optimized and with no interference from other catecholamines.